Quantifying invasion degree by alien plants species in Reunion Island. (11th May 2021) - Fenouillas, Pauline; Ah‐Peng, Claudine; Amy, Elise; Bracco, Isabelle; Dafreville, Stéphanie; Gosset, Mélodie; Ingrassia, Florent; Lavergne, Christophe; Lequette, Benoit; Notter, Jean‐Cyrille; Pausé, Jean‐Marie; Payet, Guillaume; et al.
Abstract: The largest area of intact vegetation in the Mascarene's archipelago is found on Reunion Island, but the remaining natural areas are under threats. Biological invasions are one of the main threats to biodiversity loss on this island and globally worldwide. This study aimed to quantify invasion degree by alien plants species in Reunion Island. This work was possible thanks to a large partnership between researchers and managers. All existing spatial data on invasion pattern were combined and completed by expert knowledge to develop the first 250 x 250 m map of invasion degree at the island scale. To fill the gaps where no field survey data or expert knowledge was available, we used a Random Forest model using nine climatic, landscape and anthropogenic variables. This model also provides a preliminary assessment of drivers of invasion at Reunion Island. Results showed that 85% of the extant native vegetation was invaded in different proportions; 38% are slightly invaded, 26% moderately invaded and 22% very heavily invaded. Despite the high levels of invasion in some places, more than 50% of the extant vegetation is not invaded or slightly invaded. Most of the invaded areas are located in the lowland and in the leeward coast although alien plants invade all types of vegetation from the coast to the top of the island. These results highlight a clear increase in the distribution of alien species over time. This study constitutes a key first step for about the ongoing prioritisation of management interventions on Reunion Island. Abstract : This study aimed to quantify invasion degree by alien plants species in Reunion Island using three different sources of data : data from field survey, expert knowledge and model. Résumé: La plus grande zone de végétation intacte de l'archipel des Mascareignes se situe sur l'île de La Réunion, mais les espaces naturels restants sont fortement menacés. Les invasions biologiques constituent l'une des principales menaces menant à la perte de biodiversité sur cette île et dans le monde entier. Cette étude vise à quantifier le degré d'invasion par les espèces végétales exotiques à La Réunion. Ce travail a été possible grâce à un large partenariat entre chercheurs et gestionnaires. Toutes les données spatiales existantes sur le degré d'invasion ont été combinées et complétées par du dire d'experts afin de développer la première carte (250 x250 m) rendant compte du degré d'invasion des habitats à l'échelle de l'île. Pour combler le manque d'informations (données terrain et/ou dire d'expert), nous avons réalisé un modèle statistique : Random Forest, utilisant neuf variables climatiques, topographiques et anthropiques. Ce modèle a également fourni une évaluation préliminaire des facteurs d'invasion à La Réunion. Les résultats ont montré que 85% de la végétation indigène existante est envahie dans des proportions différentes; 38% sont légèrement envahis, 26% modérément envahis et 22% très fortement envahis. Malgré des niveaux élevés d'invasion à certains endroits, plus de 50% de la végétation existante est faiblement à non envahie. La majorité des zones envahies sont situées à basses altitudes et sur la côte Ouest de l'île (sous le vent). Les plantes exotiques envahissent toutefois tous les types de végétation de la côte au sommet de l'île. Ces résultats mettent en évidence une nette augmentation de la distribution des espèces exotiques au fil du temps. Cette étude constitue une première étape clé pour la priorisation en cours des interventions de gestion sur l'île de La Réunion.